THE IMPACT OF WORKING ENVIRONMENT TOWARDS EMPLOYEE JOB SATISFACTION: A CASE STUDY IN PT. X - Tio, Edward (iBuss Management, 2014)
Employee job satisfaction is a parameter that measures the depth of Employee affectionate or positive experience derived from the work. Researchers have mentioned that employees with higher satisfaction tend to be more loyal and productive, yet there are no exact formula on maximizing employee job satisfaction, let alone a research to serve as an exact parameter of the factors influencing the job satisfaction. The writerâs purpose in this study is to examine and analyze the influence of the working environment condition towards employee job satisfaction and to provide insight on how to increase employee job satisfaction through the work environment. The writer is using the multiple regression analysis with 74 samples to measure the significance of work environment towards the job satisfaction through the distribution of questionnaire in PT. X. The result of this research shows that simultaneously work environment factors is significant towards the employee job satisfaction.Keywords: Work Environment, Job Satisfaction, Human Resource Management, Gas Industry.